Overview of bibliographic production on indigenous health and environmental policies in Brazil - Ferreira, Ana Cristina (2021)
After the 1988 Constitution, social policies gained evidence by obtaining institutional structure and resources. However, these practices were developed in disregard of the phenomena and the global understanding of the different contexts in which indigenous peoples are inserted. The lack of holistic understanding leads to failures in the provision of care and protection practices to Indigenous Peoples. Thus, this dissertation aims to analyze the state of the art of indigenous health and environmental policies in Brazil, considering the bibliographic productions and generating an overview of the application of these policies. The study is exploratory and will be produced qualitatively and quantitatively through a bibliographic survey in articles, information portals of the federal government, indigenous entities, international organizations and advice on Brazilian policies aimed at Indigenous Peoples related to health and the environment, from the colonial period up to the present time. It was possible to identify 147 health publications and 196 related to the environment, totaling 343 documents, distributed in 196 articles, 82 referring to indigenous health policies and 114 regarding environmental indigenous policies, the other publications are classified in the platforms such as doctoral theses, dossiers, master's dissertations and course conclusion works, for example. Indigenous policies aimed at increasing indigenous action and mobilization can be seen, anchored at the right and defense of the land, as well as other important demands, such as the improvement of health care and education.